O’QISH DARSLARIDA O’QUVCHILARNI IFODALI O’QISHGA O’RGATISH YO’LLARI VA VOSITALARI - Tilavova, M. (SCIENCE and SOCIETY, 2019)
In elementary classes expressive reading of literary-artistic works requires special skills and experience from the teacher and students. The article demonstrates that expressive reading is connected with speech abilities and skills. The author of the article clearly shows how to perform technical and logical tasks in teaching.